Advances in macromolecular crystallography at the Photon Factory: automation from crystallization to structural determination - Naohiro Matsugaki; Toshiya Senda (Journal of Synchrotron Radiation)
The Structural Biology Research Center (SBRC) and the Photon Factory at the High Energy Accelerator Research Organization (KEK) have played a key role in advancing macromolecular crystallography (MX) and have developed advanced experimental systems in the MX field. Key innovations include a long-wavelength MX beamline for native single-wavelength anomalous diffraction phasing (BL-1A), a crystal-shaping machine, an automated crystal-centering system and a fully automated diffraction data-acquisition system. In addition to the beamline technologies, the SBRC has developed a fully automated protein crystallization and monitoring system (PXS/PXS2). The crystallization plate prepared by PXS2 can be mounted directly onto an in situ data-acquisition system at BL-17A. These technologies have transformed experimental workflows, enabling high-throughput structure determination and supporting drug discovery. Furthermore, the SBRC can integrate advanced imaging techniques, including MX, cryogenic electron microscopy (cryo-EM) and small-angle X-ray scattering (SAXS), under one roof. This interdisciplinary approach facilitates hybrid structural analysis by combining techniques such as MX and SAXS or MX and cryo-EM.